2017
DOI: 10.1038/s41391-017-0031-8
|View full text |Cite
|
Sign up to set email alerts
|

Allopurinol and risk of benign prostatic hyperplasia in a Finnish population-based cohort

Abstract: We found that allopurinol use is associated with lowered risk of BPH medication, diagnosis and surgery. A possible explanation could be antioxidative effects of urate-lowering allopurinol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Previous clinical trials have shown that allopurinol has a positive association with prostate cancers, patients treated with allopurinol could decreased the incidence of prostate cancer. And the combined use of allopurinol for one month can reduce the level of NF kappaB in patients with colonic adenoma [16][17][18][19]. It is suggested that the drug that reduces uric acid levels have potential anticancer efects and provides a new idea for tumor treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Previous clinical trials have shown that allopurinol has a positive association with prostate cancers, patients treated with allopurinol could decreased the incidence of prostate cancer. And the combined use of allopurinol for one month can reduce the level of NF kappaB in patients with colonic adenoma [16][17][18][19]. It is suggested that the drug that reduces uric acid levels have potential anticancer efects and provides a new idea for tumor treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Our population-based cohort study did not support these findings. Although allopurinol use was associated with a lower incidence of benign prostatic hyperplasia, we did not find any differences in prostate cancer incidence [ 19 , 20 ]. Most studies evaluating possible association between allopurinol (or gout) and PCa are based on Taiwanese registries.…”
Section: Introductionmentioning
confidence: 77%
“…Previous studies mainly investigated prostate pathology related to hyperuricemia or gout. Men undergoing ULT had a lower risk of BPH than those without ULT [ 14 ]. This result is potentially explained by oxidative stress associated with hyperuricemia and the antioxidant effects of ULT.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress was considered to promote benign prostate hyperplasia (BPH) through activation of the inflammasome in response to UA [ 13 ]. Meanwhile, one population-based study demonstrated that uric acid lowering treatment (ULT) was associated with lower use of BPH medications and less frequent diagnosis of LUTS than in those who were not treated with ULT [ 14 ]. Another group found that ULT reduced prostate cancer cell growth by 37% [ 15 ].…”
Section: Introductionmentioning
confidence: 99%